Destination Image of Himachal Pradesh: Foreign Tourist Perception - Sunil Kumar; Sandeep Sharma (Centre For Tourism Planning and Development, 2021)
Destination Image is a psychological set of emotions in a tourist’s mind. This study is aninquiry from 384 Foreign Nationals who included destination Himachal in their visit toIndia. The latent factors of ‘destination image’ were extracted and validated throughstructural equation modeling (SEM). Out of the ten explored latent factors ‘affective’dimension is the major element followed by ‘infrastructure’, ‘culture’ and ‘safety’ are actingas significant persuading forces in destination image formation. The study will help variousorganizations and agencies to position their tourism products. Future researchers caninvestigate the change in destination image with other locations having the samegeographical conditions. This study is limited to the present experience of tourists anddidn’t include the revisit experiences of foreign tourists.